2018
DOI: 10.1177/1096348018817586
|View full text |Cite
|
Sign up to set email alerts
|

Creature of Habit or Embracer of Change? Contrasting Consumer Daily Food Behavior with the Tourism Scenario

Abstract: This research investigates tourist food consumption patterns and food choice motives while on trips, in comparison to their food behavior in the everyday life scenario. The results suggest that consumers’ food choice motives and behaviors during travel are inconsistent with their food regimens followed at home. In addition, gender is found to be a significant variable in explaining such inconsistencies. Implications pertaining to these findings are discussed in the context of tourism experience satisfaction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 41 publications
3
26
0
Order By: Relevance
“…Santos et al (2020) found significant changes in food types consumed between holiday settings and home, but there is also broad stability – consumption of meat, vegetables and fruit, for example changed little. Research on the relative influence of actor-related and structural or contextual variables in gastronomic practices could be very revealing, particularly if the variations between home and holiday settings are examined (Wang et al , 2019).…”
Section: Implications: Developing More Holistic Approaches To Gastronomic Experiencesmentioning
confidence: 99%
“…Santos et al (2020) found significant changes in food types consumed between holiday settings and home, but there is also broad stability – consumption of meat, vegetables and fruit, for example changed little. Research on the relative influence of actor-related and structural or contextual variables in gastronomic practices could be very revealing, particularly if the variations between home and holiday settings are examined (Wang et al , 2019).…”
Section: Implications: Developing More Holistic Approaches To Gastronomic Experiencesmentioning
confidence: 99%
“…the match between a particular food or brand and a customer’s self-image) to the psychological factors affecting tourists’ food choice (Jeong and Jang, 2018). Sociodemographic factors, such as education level, gender, ethnicity, household size, age, income and nationality and geographical origin also affect tourist food consumption (Verbeke and Lopez, 2005; Wang et al , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These and other such questions will need to be further investigated in future research. On a broader level, this study also presents a framework to investigate other types of signals that are increasingly becoming prominent in practice such as environmentally sustainable business practices (Lo et al, 2017), employee welfare (Lin & Chung, 2019), and health and wellness emphases (Wang et al, 2019). Given that signals will continue to evolve in view of the dynamic sociocultural and economic conditions, this study offers insights into the value of comparing and contrasting the value associated with each such signal, or a combination thereof.…”
Section: Discussionmentioning
confidence: 99%